Development of Solar System Teaching Aids with Manipulative Virtualization Concrete and Digital Augmented Reality - Wiyanto, Wiyanto; Miftakhul Falah, Muhammad; Ardian Awaluddin; Muhammad Sholikhan (Universitas Negeri Semarang, 2024)
Teaching aids are used to explain the concept of science learning in the form of real objects. Along with the development of Information and Communication Technology (ICT), the specifications for teaching aids need innovation, especially digital access and Augmented Reality (AR) based virtualization, which are currently growing rapidly. This research aims to develop a solar system teaching aids with manipulative virtualization concrete and digital AR. The ADDIE Research and Development (R and D) model has been applied to achieve the objectives of this study. The stages of this research were carried out through the stages of Analysis, Design, Development, Implementation and Evaluation. This research has produced a solar system teaching aids with manipulative virtualization concrete and digital AR. The results of the validation of content experts are 88%, validation of media and technology experts are 86% and teacher or user responses are 88%. The three validations reached the very feasible criteria. The average percentage of the validation score is 87.33% or the criteria are very feasible. It is concluded that the solar system teaching aids with manipulative virtualization concrete and digital AR are valid to be used in science learning to improve the science concepts comprehensions, especially solar system.